Avaliação da hemocompatibilidade de revestimentos poliméricos de quitosana sulfatada sobre ligas metálicas de aço inoxidável e ligas de titânio modificadas com crescimento de nanotubos de TiO2 - Gomes, Sandy Danielle Lucindo (2023)
According to the World Health Organization, cardiovascular diseases (CVD) kill 17.7 million people each year, corresponding to 31% of all global deaths in 2020, thus, the increase in cardiovascular diseases has been driving the use of coronary stents. The current treatment includes metallic stents covered with a polymeric matrix rich in immunosuppressive drugs such as rapamycin that, although they contribute to a reduction in restenosis, present the formation of clots and thrombi late. Metal stents, when interacting with blood, can often suffer corrosion of the material and favor the formation of thrombi at the implantation site resulting in device failure. In order to improve the performance of these devices, modified chitosan has recently been proposed as a polymeric coating increasing the hemocompatibility of the metallic surfaces of cardiovascular stents. Indeed, chitosan is a biocompatible polymer with amino and hydroxyl groups along the chain, thus facilitating its chemical modification. In this work, polymeric coatings of sulfated chitosan (QS) were produced on 316L stainless steel and titanium alloys (Ti10Mo8Nb6Zr) modified with TiO2 nanotubes growth, in addition, a comparative study with natural chitosan was carried out. Initially, natural chitosan (QN) was sulfated with chlorosulfonic acid, then sulfated and natural chitosan films cross-linked or not with glutaraldehyde were developed for cytotoxicity evaluation. Subsequently, the metal surfaces commercially used for cardiovascular stent production, stainless steel and titanium alloys, were covered with sulfated chitosan and natural chitosan by means of a polydopamine layer and a polyethylene glycol bonding arm. The sulfated chitosan developed showed in the FTIR spectrum the bands referring to the sulfated groups added in the polymer chain, moreover at the concentration of 200 µg/mL the material was able to prolong the clotting time by 2.5 times when compared to the control and natural chitosan. In addition, unlike natural chitosan, sulfated chitosan was not able to induce platelet aggregation and the sulfated chitosan and natural chitosan films containing the lowest concentration of glutaraldehyde agent (0.03% v/v) were not toxic to L929 cells (fibroblasts). Through the platelet adhesion assay, it was possible to identify that, among the metallic surfaces, titanium surfaces showed greater hemocompatibility when compared to stainless steel samples, presenting a lower percentage of area covered by platelets 27.2 ± 4.9 versus 60.5 ± 4.3. Regarding the coatings, the metallic surfaces coated with sulfated chitosan presented a lower platelet activation, being the titanium surface coated with sulfated chitosan the sample that presented the lowest percentage of platelet coverage (13.7% ± 3.5), inferring that this was the material that presented the greatest potential for the coating of medical devices that remain in contact with the blood and that may assist in the treatment of cardiovascular diseases. In addition, this device showed potential advantages compared to stents currently on the market.